2019
DOI: 10.21513/2410-8758-2019-2-45-65
|View full text |Cite
|
Sign up to set email alerts
|

Tendencies in Changes of Climate Extremality in Western Siberia at the End of the Xx Century and the Beginning of the Xxi Century

Abstract: Институт мониторинга климатических и экологических систем СО РАН, Российская Федерация, 634055, г. Томск, пр. Академический, 10/3; kh_ev@mail2000.ru Реферат. В данной работе за временной интервал 1976-2016 гг. проведен анализ межгодовой изменчивости среднесезонных значений температуры воздуха, скорости ветра, количества атмосферных осадков и их экстремумов для Западной Сибири отдельно для севера и юга территории, а также для Томской области. Исследование проводилось по данным наблюдений на метеорологически… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…That means that the distribution was right-skewed, righttailed, or skewed to the right, which may indicate a decrease in precipitation values for the considered period and an increase in the frequency of extreme events with increased precipitation. This confirmed the results that were obtained earlier in Reference [12]. In the warm season, only the GPCC dataset represented a positive skewness.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…That means that the distribution was right-skewed, righttailed, or skewed to the right, which may indicate a decrease in precipitation values for the considered period and an increase in the frequency of extreme events with increased precipitation. This confirmed the results that were obtained earlier in Reference [12]. In the warm season, only the GPCC dataset represented a positive skewness.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, most of the territory is characterized by an increase in the number of days with heavy snowfall [9]. Thus, in Western Siberia, there is an increase in extreme precipitation in the winter and a tendency toward dry periods in the summer [12]. In the south of the region, the risks of heavy and long-term precipitation increase [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since warming means that the atmosphere has more energy than previously, warming leads to an increase in frequency and magnitude of various extreme weather events (Table 1 ) dissipating this excess energy. These weather events have increased since the mid-1990s in Western Siberia causing significant damage to the economy and people (Evseeva and Romashova 2011 ; Aleseev et al 2014 ; Kharyutkina et al 2019 ; Appendix S1 ). Emergencies resulting from the development of deep mesoscale convection, such as thunderstorms, hail, squalls, and tornados, have been more frequent than before 2000, and increased convective atmospheric instability has been recorded (Gorbatenko et al 2020 ).…”
Section: Extreme Weathermentioning
confidence: 99%
“…Lodging com plicates mechanized harvesting, which results in additional yield loss. The weather conditions monitoring carried out in Western Siberia from 1976 to 2016 has shown that the regional climate has become more extreme, so its increased frequency of gales, showers and thunderstorms significantly reduces the yield (Kharyutkina et al, 2019). Considering this unfavorable weather conditions, it becomes essential to create the wheat varieties that are resistant to lodging.…”
Section: Introductionmentioning
confidence: 99%